Diagnosis of a complicated cervical injury in the craniocerebral region of the cervical spine at a late period - Pishanov, Ruslan; Goncharuk, Oksana; Kasyanov, Valeriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
On the basis of an analysis of 156 observations of patients with a complicated cervical injury in the craniocerebral region of the cervical spine within a late period it was found out that a combined examination made it possible to reveal an extent of the spinal cord damage and structural-functional changes in the vertebral column, which are very important for determining subsequent therapeutic tactics and prognosis. It was shown that classical radiological examination should be supplemented with modern neurovisualizing examinations: CT and MRI.